On‐Demand Wrinkling Patterns in Thin Metal Films Generated from Self‐Assembling Liquid Crystals. (28th December 2014) - de Haan, Laurens T.; Leclère, Philippe; Damman, Pascal; Schenning, Albertus P. H. J.; Debije, Michael G.
Abstract : In this work, a new, universal method is described that uses the photopatterning of liquid crystals, which is accurately translated into a controlled, intricately wrinkled metal surface. Remarkably, the patterns have an oscillation in amplitude of the wrinkles. This rapid method allows generation of intricate multidomain patterns and continuous circular structures, including azimuthal, radial, and even higher complexity arrangements as examples. These wrinkled gold surfaces are also strikingly visual, which is interesting for applications ranging from diffractive elements to fine jewelry. Abstract : Unique wrinkling patterns with oscillating amplitudes in any arbitrarily complex fashion are generated by controlling the alignment director of a liquid crystal network using photoalignment layers in combination with photomasks. The wrinkled gold surfaces are strikingly visual which is interesting for applications ranging from diffractive elements to fine jewelry. Image adapted with permission. Copyright 1973, Pink Floyd Music Ltd.